Pengaruh Implementasi Pendidikan Agama Islam terhadap Potensi Kreativitas dan Inovasi Beragama Siswa di Kelas X MA Swasta Al-Wasliyah Teluk Pulai Luar Kecamatan Kualuh Leidong Kabupaten Labuhan Batuutara - Nadrah, Nadrah; Marisa, Siti; Rahman, Abdul (Lembaga Yasin AlSys, 2025)
The purpose of this research is to determine the implementation of Islamic Religious Education (PAI) in developing the religious creativity potential of Class X students at MA Swasta Al-Wasliyah Teluk Pulai Luar, Kec. Kualuh Leidong, Labuhan Batu Utara Regency. It also aims to examine the influence of Islamic Religious Education implementation on developing the religious innovation potential of Class X students at the same school. Furthermore, the research seeks to measure the extent to which the implementation of Islamic Religious Education influences the development of religious creativity potential in these students. The research method used is quantitative, with a sample of 35 students. sThe results of this study indicate that the implementation of Islamic Religious Education in developing the religious creativity potential of Class X students at MA Swasta Al-Wasliyah Teluk Pulai Luar is carried out through classroom learning processes, role modeling by teachers, and the application of religious activities outside of class hours. There is an impact of Islamic Religious Education implementation in developing the religious innovation potential of these students, as shown by the t-value being greater than the t-table value (5.544 > 1.690). The magnitude of the impact of Islamic Religious Education implementation on developing the religious creativity potential is 48.2%, based on the determinant test.